2011
DOI: 10.1007/s00264-011-1335-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential of exogenous cartilage proteoglycan as a new material for cartilage regeneration

Abstract: Background Although proteoglycan (PG) is one of the major components of cartilage matrices, its biological function is not fully elucidated. Methods The objectives of this study were to investigate the proliferation and differentiation of chondrocytes embedded in atelocollagen gel with exogenous cartilage PG (PGatelocollagen gel) in vitro, and also to evaluate the repair of cartilage defects by PG-atelocollagen gel in vivo. In the in vitro study, rabbit chondrocytes were cultured in the PGatelocollagen gel. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, the core protein of acetic acid-extracted salmon PG is partially fragmented compared to that of GdnHCl-extracted salmon PG [12] . Although the acetic acid-extracted PG is the fragmented CSPG fraction, it retains various biological activities and is the only commercially available PG for pharmacological use [13] , [14] , [15] , [16] , [17] . In this study, we show that salmon PG reduces the tube-like formation of vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, the core protein of acetic acid-extracted salmon PG is partially fragmented compared to that of GdnHCl-extracted salmon PG [12] . Although the acetic acid-extracted PG is the fragmented CSPG fraction, it retains various biological activities and is the only commercially available PG for pharmacological use [13] , [14] , [15] , [16] , [17] . In this study, we show that salmon PG reduces the tube-like formation of vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, salmon nasal cartilage proteoglycan has the potential to induce the proliferation of chondrocytes and the production of proteoglycans by chondrocytes in vitro (29,30) and also exhibits anti-inflammatory action in vivo in arthritic mice (31). Thus, it was proposed that the administration of salmon nasal cartilage proteoglycan may improve the symptoms of knee osteoarthritis, due to its chondroprotective and anti-inflammatory actions.…”
Section: Introductionmentioning
confidence: 99%
“…A previous open-label (unblended) study by the current authors investigating individuals with knee osteoarthritis indicated that administration of proteoglycan extracted from salmon nasal cartilage alleviates the symptoms of knee osteoarthritis, possibly by reducing the degradation of type II collagen, as evidenced by a reduction in the C2C/PIICP ratio ( 29 ). Notably, salmon nasal cartilage proteoglycan has the potential to induce the proliferation of chondrocytes and the production of proteoglycans by chondrocytes in vitro ( 29 , 30 ) and also exhibits anti-inflammatory action in vivo in arthritic mice ( 31 ). Thus, it was proposed that the administration of salmon nasal cartilage proteoglycan may improve the symptoms of knee osteoarthritis, due to its chondroprotective and anti-inflammatory actions.…”
Section: Introductionmentioning
confidence: 99%
“…PG or its metabolites may exert anti-inflammatory actions via the suppression of inflammatory cytokine production, as well as a chondroprotective effect at the joint tissue via the proliferation of chondrocytes and the production of PGs. 10 In an in vivo study by Yo Tsuchiya et al, PG was shown to be absorbed through the small intestine via clathrin-mediated endocytosis. 11 There are also many instances, such as genetic disorders, where changes in PG production directly affect cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%